2006
DOI: 10.1021/bi060409m
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Dynamics, and Stability Variation in Bacterial Albumin Binding Modules:  Implications for Species Specificity,

Abstract: Protein G-related albumin-binding (GA) modules are frequently expressed on the surfaces of bacterial cells. The limited amino acid sequence variation among GA modules results in structural and functional differences with possible implications for bacterial pathogenesis and host specificity. In particular, the streptococcal G148-GA3 and F. magna ALB8-GA albumin-binding domains exhibit a degree of structural and dynamic diversity that may account for their varied affinities for different species of albumin. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…22) was used to build the model of the hypothetical 4b1a form of PSD-1 using the homology modeling program NEST (23). Then, flexible docking simulations were used to dock a Myr molecule onto both the a-helical form of the GA module PSD-1 (PDB code 2FS1) (24) and the modeled 4b1a form. Figure 2 shows the lowest energy complexes obtained using the AutoDock Vina molecular docking software (25).…”
Section: Discussionmentioning
confidence: 99%
“…22) was used to build the model of the hypothetical 4b1a form of PSD-1 using the homology modeling program NEST (23). Then, flexible docking simulations were used to dock a Myr molecule onto both the a-helical form of the GA module PSD-1 (PDB code 2FS1) (24) and the modeled 4b1a form. Figure 2 shows the lowest energy complexes obtained using the AutoDock Vina molecular docking software (25).…”
Section: Discussionmentioning
confidence: 99%
“…NMR Spectroscopy. 15 N-and 13 C/ 15 N-labeled samples were prepared at 0.2-0.3-mM concentrations in 100 mM KPO4 buffer (pH 7.2) containing 10 mM sodium azide and 5-10% D 2O. NMR spectra were collected on a Bruker AVANCE 600 MHz spectrometer fitted with a z axis gradient 1 H/ 13 C/ 15 N triple resonance cryoprobe.…”
Section: Methodsmentioning
confidence: 99%
“…The A52F mutation causes an Ϸ10-fold decrease in HSA-binding affinity (data not shown), which may be partly due to these small structural changes. Previous work showed that the affinity of G A modules for albumins can be affected by relatively small changes in helical arrangement (25). Most core residues are situated similarly in both proteins apart from those in the ␣3-helix that are displaced 2-3 Å from their wild-type PSD-1 positions.…”
mentioning
confidence: 93%